The Peer Group Effect on Drug Abuse and Academic Performance Among University Student - Abdallah, Ahmed Saied Rahama; Mohammed, Mohammed Omar Musa (Journal of Ecohumanism, 2024)
The drug problem is one of the most complex problems in the world, and hardly any society is devoid of it, whether in developed or developing countries. It threatens students' social, economic, and educational life at all levels. Saudi Arabia like the other countries faces drug spread among the youth. This study aims to assess the role of peer group effect on drug abuse and academic performance among university students in the Hawtat Bani Tamim. The study adopts the questionnaire as a tool for collecting data. The sample size of the study was 121 participants from university students. The study adopted descriptive statistics and inferential statistics. The results of the study found that the prevalence of drug abuse among university students was 8.3. There is a significant relationship between drug abuse and several factors under investigation. Notably, there were notable connections identified between drug abuse and age, the availability of drugs, and parental influence status. Also, the result showed that drug abuse delays graduation and absence from university. Peer group pressure influences drug abuse among students and plays a crucial role in drug abuse among university students. The study recommends providing programs that encourage students to quit drug abuse.